Perancanganan Sistem Toko Apip Collection Konveksi Baju Berbasis Web Menggunakan Metode Waterfall - Gading Islam; Muhamah Fathi Farhat; Yuda Pebrian; Saprudin, (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2024)
This research aims to design a web-based Apip Collection store system specializing in clothingmanufacturing using the Waterfall method. The Waterfall method involves structured stages, starting from in-depth analysis of user requirements to system implementation, testing, and maintenance. The designed systemaims primarily to simplify sales management, optimize product inventory, and enhance interaction andservice to customers. Implementation of this web-based system is expected to provide benefits such asimproved operational efficiency through more structured processes and responsiveness to market needs. Comprehensive system testing is conducted to ensure that all features and functionalities operate according to established standards. The research results indicate that the designed web-based store system effectively meets Apip Collection's needs in managing and expanding clothing manufacturing business operations more effectively and efficiently, providing a better shopping experience for customers.